A cavalaria no discurso político castelhano-leonês no final doséculo XIII início do século XIV: entre vínculo social e forma de vida virtuosa - Olga Pisnitchenko (2016)
In this work we analyze the political discourse created around the chivalry at the end of the thirteenth century, which from this time came to be recognized as one of the three estates of the Leonese-Castilian kingdom. As a counterpart to the primary discourse elaborate by themonarch we are also considering the nobleman's' treatises belonging to the beginning of the fourteenth century. We showed that by entering a knighthood in the system of political thinking of the Leonese-Castilian kingdom royal discourse introduced the chivalry as one of the links in the social relations system, whose top is occupied by the monarch. At the same time, the noble discourse, which we studied by the texts of Don Juan Manuel, conditions knighthood by virtuous way of life, thus, dividing the chivalry and the king's service, that is an non-shared notions in the previous concept. In search of chivalric model built by the original royal discourse were analyzed as legislative as historical works written during the reign of Alfonso X which along with documents relating to distributions and donations of the conquered lands have helped us to create a picture of political actions of Alfonso X with regards chivalry. We follow the transformation of this process till the first half of the fourteenth century, when Alfonso XI adopting the discourse of his great-grandfather creates the Orden de la Banda and shortly after this makes himself a knight and then the other important people of his kingdom. Thus, adding to vassal also chivalry linkage between the king and the nobility. Bearing in mind this historical and political landscape were analyzed the works of Don Juan Manuel, the main political opponent of Alfonso XI and the initiator of the idea of not associated with the king chivalry.